The SABC and Afrikaans news - Elise van Staden (Communicare)
Afrikaans and English television news started in 1975 with equal airtime. In 1996 after an SABC policy change, the Afrikaans TV news bulletin was relegated to a lesser and infrequent time slot. Many Afrikaans-speaking viewers perceived these changes as a threat to the future of Afrikaans and pressure was exerted by cultural organizations and Afrikaans newspapers. There are also indications that economy of language played a major role in the re-establishment of a regular time slot for Afrikaans television news. Economy of language is a field of study probing the relationship between linguistic and economic variables. The role of language in people’s involvement in the economy is diverse but fundamental. On the one hand language empowers or disempowers people to join the national economy, and on the other hand people’s language preferences sometimes determine their consumer decisions. The SABC’s Afrikaans television news is a prime example of language preference becoming an economic determinant.